2002
DOI: 10.1002/1521-3757(20020715)114:14<2690::aid-ange2690>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 2‐Butyne with nido ‐[1,2‐(Cp*RuH) 2 B 3 H 7 ]: Improved Kinetic Control Leads to Metallacarboranes of Novel Composition and Structure

Abstract: The conventional route to metallacarboranes proceeds in a sequence of steps leading from polyborane to carborane to metallacarborane. [1±4] Although a fruitful strategy, it is also one in which strong bonds are formed before weak ones. Access to more diverse chemistry might arise by adoption of the reverse strategy, that is, formation of BÀB/BÀM before B À C/M À C bonds, thereby generating the most stable products quenched with 10 % perchloric acid (10 ml) and then extracted with CH 2 Cl 2 . The solvent was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Heating up to 80°C leads to decomposition rather than conversion from one to the other confirming the existence of a substantial barrier to interconversion. The two isomers are analogous to the clusters A and B generated from the methyl propiolate reaction [15] and shown in Scheme 1 as C is the analog of the antiMarkovnikoff addition of the alkyne. Based on our interpretation of the conversion of A and B to C-O inserted products, the barrier to isomer conversion in this system is lower than that for 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heating up to 80°C leads to decomposition rather than conversion from one to the other confirming the existence of a substantial barrier to interconversion. The two isomers are analogous to the clusters A and B generated from the methyl propiolate reaction [15] and shown in Scheme 1 as C is the analog of the antiMarkovnikoff addition of the alkyne. Based on our interpretation of the conversion of A and B to C-O inserted products, the barrier to isomer conversion in this system is lower than that for 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that a metal plays a critical role. For example, the dirhodaborane leads predominantly to catalytic cyclotrimerization of alkynes [10,11]; the diiridaborane needs a molybdenum center to promote alkyne insertion [12]; and the diruthenaborane, nido-1,2-(Cp * RuH) 2 B 3 H 7 (1) leads to diverse, unprecedented products even at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we and others became interested in these types of Ôconverse reactionsÕ of acetylenes with boron-containing clusters, using both metallaborane and heteroborane substrates [5][6][7][8][9][10][11]. It was found, for example, that the incorporation of HC"CH into the arachno nine-vertex [4,4,4,4-(CO)(PPh 3 ) 2 H-4-IrB 8 H 12 ] cluster gives an 11-vertex {IrC 2 B 8 } species, and that HC"CAC(Me)@CH 2 gives both 10-vertex {IrCB 8 } and 11-vertex {IrC 2 B 8 } species [7,8].…”
mentioning
confidence: 99%
“…Of the few examples, it had been shown that addition of alkynes, accompanied by boron-vertex loss, to [2-(C 5 H 5 )-nido-2-CoB 4 H 8 ] gives [1-(C 5 H 5 )-nido-1,2,3-CoC 2 B 3 H 7 ] and Csubstituted derivatives [3], and that the addition of MeC"CMe into [1,1,1-(CO) 3 [4]. More recently, we and others became interested in these types of Ôconverse reactionsÕ of acetylenes with boron-containing clusters, using both metallaborane and heteroborane substrates [5][6][7][8][9][10][11]. It was found, for example, that the incorporation of HC"CH into the arachno nine-vertex [4,4,4,4- [7,8].…”
mentioning
confidence: 99%